Risk of transient vision loss after intravitreal aflibercept using vial-prepared vs. the novel prefilled syringe formulation - Klaas, Julian E.; Bui, Vinh; Maierhofer, Niklas; Schworm, Benedikt; Maier, Mathias; Priglinger, Siegfried G.; Siedlecki, Jakob (Frontiers in Medicine, 2023)
Purpose To compare the risk of transient vision loss (TVL) probably attributable to a severe intraocular pressure spike after intravitreal aflibercept application using the novel prefilled syringe (PFS) vs. the established vial system (VS). Methods Datasets of the intravitreal injection service of the Ludwig Maximilians-University Munich and the Technical University Munich, Germany, were screened for documentation of TVL after intravitreal injection of aflibercept. The observation period included two full months prior to the introduction of the novel PFS and two months afterwards. TVL was defined as loss of perception of hand motion for a duration of >30 s. Results Over a period of four months, 1720 intravitreal injections of aflibercept were administered in 672 patients. There were 842 injections with the old VS, and 878 injections using the novel PFS. Using the VS, TVL was noted during two injections (0.24%) in two patients, as compared to 11 cases of TVL (1.25%) in 10 patients with the PFS (p = 0.015). Using the PFS, patients had a 5.3-fold risk of TVL as compared to the VS (OR: 5.33; 95% CI: 1.2–24.1; p = 0.0298). Conclusion There was a more than five-fold risk of TVL using the novel pre-filled aflibercept syringe as compared to the established vial system. During informed consent, this risk should be discussed.